The Justiciability of Social Rights in Morocco and France: La Justiciabilité des Droits Sociaux au Maroc et en France - Mesbah, Jamal (Journal of Legal Studies and Researches, 2020)
Justiciability is a new idea and is in the process of taking root, the idea of submitting a challenge to violations of social rights to a judicial body; including the goal of building an order concerned with equity and social democracy. The current evolution is positive so that the social rights are finally recognized as fundamental rights. La justiciabilité est une idée neuve et en cours d'enracinement l’idée de soumettre la contestation des violations des droits sociaux à une instance juridictionnelle; dont le but de la construction d'un ordre soucieux d’équité et de démocratie sociale. L’évolution en cours est chargée de sens ce que les droits sociaux se voient reconnaître enfin le caractère des droits fondamentaux.